Nurses’ Challenges and Strategies for Enhancing Care Quality and Safety - Alzahrani, Abdullah Saleh Ahmed; Shehri, Salha Ali Al; Aljazzar, ‏Ruwaida Abdullah; Alharbi, Ahlam Zainalabdeen; Alshmmary, Dalal Thweeb Daghish; Alshammarl, Mashael Fallag Ageel; Al Enzy, Rasha Lafi Mejze; Alenzi, Seham Lafi Mejze; Al Enzy, Asma Lafi Mejze; Alenazi, Abeer Fahad Farhan; et al. (Journal of Posthumanism, 2024)
The global healthcare landscape continually emphasizes the critical importance of high-quality and safe patient care, with nurses serving as the foundational providers at the point of care, significantly influencing patient outcomes. Persistent issues, including adverse events, patient dissatisfaction, and nursing workforce challenges, necessitate a comprehensive understanding of the obstacles nurses face and the strategies they employ to uphold standards. The objective of this review was to systematically synthesize existing literature to identify the principal challenges encountered by nurses and explore effective strategies for enhancing the quality and safety of care delivery. This integrative literature review, utilizing a rigorous systematic approach to collate findings from diverse international studies, revealed that major challenges include pervasive occupational burnout, suboptimal nurse-to-patient staffing ratios, communication breakdowns, and a poor organizational work environment. Key strategies identified for enhancing care quality and safety center on fostering supportive work climates, implementing robust staffing policies, utilizing professional development programs focused on precision health and safety competencies, and strengthening interprofessional collaboration. The major recommendation is for healthcare systems to implement multi-faceted, nurse-centered interventions that address both systemic and individual factors. In conclusion, addressing nurses’ challenges through strategic, evidence-based initiatives is essential for improving the nursing work environment, which directly correlates with enhanced patient care quality and safety. The implications of these findings are substantial for healthcare policymakers and organizational leadership, guiding targeted resource allocation and policy development.